2020
DOI: 10.1038/s42003-020-1103-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic microenvironment shapes HIV-1 replication and latency

Abstract: Viral replication is defined by the cellular microenvironment and one key factor is local oxygen tension, where hypoxia inducible factors (HIFs) regulate the cellular response to oxygen. Human immunodeficiency virus (HIV) infected cells within secondary lymphoid tissues exist in a low-oxygen or hypoxic environment in vivo. However, the majority of studies on HIV replication and latency are performed under laboratory conditions where HIFs are inactive. We show a role for HIF-2α in restricting HIV transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 92 publications
0
26
1
Order By: Relevance
“…There is evidence to suggest that this profound hypoxemia may alter the ability of SARS-CoV-2 to infect host cells. Hypoxia has been reported to regulate the replication of a number of viruses ( Jiang et al., 2006 ; Kraus et al., 2017 ; Zhao et al., 2020a ; Zhuang et al., 2020 ), enhancing the replication of Epstein-Barr virus ( Jiang et al., 2006 ; Kraus et al., 2017 ), but suppressing HIV and influenza infection ( Zhao et al., 2020a ; Zhuang et al., 2020 ), demonstrating that the interaction between hypoxia signaling and viral infection is context specific and dependent on both the host cell and viral species. Furthermore, hypoxia has been reported to either induce or, in some cases, suppress ACE2 expression in lung pulmonary arterial smooth muscle cells (PASMCs) ( Zhang et al., 2009 , 2019 ), hematopoietic stem cell precursors ( Joshi et al., 2019 ), and hepatocarcinoma cells ( Clarke et al., 2014 ).…”
Section: Main Textmentioning
confidence: 99%
“…There is evidence to suggest that this profound hypoxemia may alter the ability of SARS-CoV-2 to infect host cells. Hypoxia has been reported to regulate the replication of a number of viruses ( Jiang et al., 2006 ; Kraus et al., 2017 ; Zhao et al., 2020a ; Zhuang et al., 2020 ), enhancing the replication of Epstein-Barr virus ( Jiang et al., 2006 ; Kraus et al., 2017 ), but suppressing HIV and influenza infection ( Zhao et al., 2020a ; Zhuang et al., 2020 ), demonstrating that the interaction between hypoxia signaling and viral infection is context specific and dependent on both the host cell and viral species. Furthermore, hypoxia has been reported to either induce or, in some cases, suppress ACE2 expression in lung pulmonary arterial smooth muscle cells (PASMCs) ( Zhang et al., 2009 , 2019 ), hematopoietic stem cell precursors ( Joshi et al., 2019 ), and hepatocarcinoma cells ( Clarke et al., 2014 ).…”
Section: Main Textmentioning
confidence: 99%
“…Under hypoxic conditions, HIV replication and transcriptional activity were significantly reduced compared with normoxic conditions. In specific strains of HIV that contain HREs in their long terminal repeat (LTR) regions, the interaction between HREs and the HIF-2α–HIF-1β complex results in inhibition of HIV replication ( 30 ). However, studies analyzing HRE-deficient HIV strains and in vivo experiments would be needed to further characterize the relevance of oxygen tension on HIV infection.…”
Section: Viral Invasion Strategies In Hypoxiamentioning
confidence: 99%
“…This phenomenon interferes with the recognition and targeting of infected cells following viral activation — a strategy utilized for the development of potential therapeutics ( 62 ). Therefore, combination therapies that target HIF-2α or enhance the activity of HIF inhibitors may be useful in treating particular HIV strains ( 30 ).…”
Section: Therapeutic Antiviral Strategies Targeting Hif Signalingmentioning
confidence: 99%
“…Further, a recent CRISPR-based knockout screen by Rathore et al (2020) revealed the role of several host deubiquitinases such as UCH37, USP14, OTULIN, and USP5 in HIV-1 latency. In the lymph node, where oxygen availability is less, Zhuang et al (2020) showed that hypoxia-inducible factor 2α (HIF2α) binds to LTR, suppresses the transcription, and promotes latency. These studies further await independent confirmations on the factors identified to regulate the latency.…”
Section: Transcription and Latencymentioning
confidence: 99%